Troponin I level in risk stratification of non-ST-elevation myocardial infarction in smokers - Iram Shahriar; Shahina Sobhan; Ziarrat Islam (Bangladesh Pharmacological Society, 2011)
A prospective study was carried out to evaluate the role of troponin I in risk stratification of non-ST-elevation myocardial infarction in 40 smoker and 40 non-smoker patients. The troponin I was significantly higher (p<0.001) in smokers (35.5 ± 5.22 ng/mL) than non-smoker (0.27 ± 0.01 ng/mL). The duration of hospital stay was longer in Group I (106.6 ± 2.36 hour) than in Group II (49.20 ± 1.01 hour). The major adverse cardiac event was higher in smoker (71.79%) compared to non-smokers (10.8%). So, it may be concluded that higher value of troponin I with history of smoking in non-ST-elevation myocardial infarction may be considered as 'high risk group' patients.